KOMPETENSI ABSOLUT DAN RELATIF PERADILAN TATA USAHA NEGARA MENURUT UNDANG-UNDANG NOMOR 5 TAHUN 1986 Jo. UNDANG-UNDANG NOMOR 9 TAHUN 2004. - Aspani, Budi (Solusi, 2018)
ABSTRACT Indonesia is constitutionally constitutional state and requires the government through its apparatus in the field of State Administration to play a positive active role in all aspects of people's lives to achieve the prosperity of their people. Within this framework, it is not uncommon for a dispute to be caused by actions from the government in the form of irregularities, thus violating the human rights of its citizens. Strictly speaking, these deviations constitute government actions that are detrimental to those affected by the decision, in this case the people. The foregoing raises problems namely; whether any decision of the State Administration or Agency that causes harm to a person or legal entity can be submitted and sued as a dispute to the State Administrative Court and administrative efforts in which the decision can be sued again through the State Administrative Court. In this study the authors use the method of normative law research (normative law research) and by using primary, secondary and tertiary legal materials. Normative legal research examines laws that are conceptualized as the norms or principles that apply in society, and become a reference for each person's behavior. Management and analysis of data is done in a qualitative way that is analyzing library data to produce descriptive data. After conducting discussions on the existing problems, it can be concluded, Each decision of the State Administration Agency or officials that causes harm to civil legal persons or entities can be submitted and sued as a dispute to the State Administrative Court. Its relative competency is related to the place of residence or jurisdiction of the court itself, as well as the parties to the dispute. Whereas the absolute competence can be seen from the point of view of the basis of disputes, which is due to the issuance of written provisions by the State Administrative Court or Agency. Administrative efforts in resolving state administrative disputes are known as administrative channels or efforts, whether in the form of administrative appeals or objections. In accordance with the basis of our country's philosophy of Pancasila, then the state administrative disputes should be resolved as far as possible through administrative efforts, which are more deliberative in reaching consensus. But if all available administrative efforts have been used, it turns out that the disputing parties remain unsatisfied, then the matter is raised and sued through the State Administrative Court.